Effect of Prescribed Fire and Mechanical Treatments on Northern Bobwhite Occupancy in Mesic Pine Flatwoods - Sarah K Brown; William E. Palmer (National Quail Symposium Proceedings, 2022)
We examined whether roller-chopping, mowing, and prescribed fire used to restore groundcover in pine flatwoods habitats affected northern bobwhite (Colinus virginianus; hereafter, bobwhite) occupancy. We surveyed bobwhites using repeated point counts (n = 3), April–June each year, to determine response to prescribed fire and mechanical treatments on Osceola National Forest (Osceola, 78 plots) and St. Sebastian River Preserve State Park (Sebastian, 11 plots) in Florida, USA, 2013–2019. We measured groundcover each year at randomly placed transects within 200-m radius point-count plots. To assess the importance of management covariates, we fit single season occupancy models to predict occupancy (ψ) and detection (p). Detection probability was 0.12 (standard error [SE] = 0.05) and 0.35 (SE = 0.05) on Osceola and Sebastian, respectively. Modeled occupancy on both sites was best predicted by presence of roller-chopping, years since fire, and year. Predicted occupancy was highest on plots with 1 year since fire (Osceola, 0.22 [SE = 0.10]; Sebastian, 0.67 [SE = 0.18]). Predicted occupancy was higher on roller-chopped plots (Osceola, 0.33 [SE = 0.15]; Sebastian, 0.85 [SE = 0.15]) than on mowed (Osceola, 0.08 [SE = 0.03]) or untreated plots (Osceola, 0.07 [SE = 0.03]; Sebastian, 0.38 [SE = 0.34]). Roller-chopping and fire reduced density of palmetto (Seranoa spp.)-shrub vegetation and increased grasses and forbs. To increase bobwhite occupancy and improve habitat suitability of degraded mesic pine flatwoods, we recommend roller-chopping and a 2-year fire frequency.
Keywords: Colinus virginianus; habitat; management; mowing; northern bobwhite; occupancy; pine flatwoods; prescribed fire; roller-chopping.